ESTIMASI STOK KARBON MANGROVE STRATA POHON DI KELURAHAN TRIMULYO KOTA SEMARANG SEBAGAI UPAYA KONSERVASI MANGROVE - Arterio Furqon Hadidi (LPPM Universitas Negeri Jakarta, 2022)
Development progress that occurred in the city of Semarang has an impact on increasing community economic activity. This increasing carbon emissions in the air occured due to the use of fossil fuels. One of the efforts to reduce carbon emissions is by reforestation. The city of Semarang has 19.541 hectares (52.31%) of green open space out of 37.303,9 hectares of the total area of the city. However, the area of the mangrove ecosystem in Semarang City was only 68,13 Ha. Even though mangrove ecosystems have a higher ability to absorb carbon than other ecosystems. Based on these conditions, it was necessary to estimate mangrove carbon stocks as an effort to determine the potential of mangrove tree strata to absorb carbon. From the results, the value of mangrove carbon stocks in the Trimulyo mangrove ecosystem of 36,00 tons/ha had the potential to act as a carbon sink.